Cytochrome P450 CYP2E1 Suppression Ameliorates Cerebral Ischemia Reperfusion Injury - Jin Yu; Hong Zhu; Mark S. Kindy; Saeid Taheri (MDPI AG, 2021)
Despite existing strong evidence on oxidative markers overproduction following ischemia/reperfusion (I/R), the mechanism by which oxidative enzyme Cytochrome P450-2E1 (CYP2E1) contributes to I/R outcomes is not clear. In this study, we sought to evaluate the functional significance of CYP2E1 in I/R. CYP2E1 KO mice and controls were subjected to middle cerebral artery occlusion (MCAo-90 min) followed by 24 h of reperfusion to induce focal I/R injury as an acute stage model. Then, histological and chemical analyses were conducted to investigate the role of CYP2E1 in lesion volume, oxidative stress, and inflammation exacerbation. Furthermore, the role of CYP2E1 on the blood-brain barrier (BBB) integrity was investigated by measuring 20-hydroxyecosatetraenoic acid (20-HETE) activity, as well as, in vivo BBB transfer rate. Following I/R, the CYP2E1 KO mice exhibited a significantly lower lesion volume, and neurological deficits compared to controls (p < 0.005). Moreover, reactive oxygen species (ROS) production, apoptosis, and neurodegeneration were significantly lower in the CYP2E1(−/−) I/R group (p < 0.001). The BBB damage was significantly lower in CYP2E1(−/−) mice compared to wild-type (WT) (p < 0.001), while 20-HETE production was increased by 41%. Besides, inflammatory cytokines expression and the number of activated microglia were significantly lower in CYP2E1(−/−) mice following I/R. CYP2E1 suppression ameliorates I/R injury and protects BBB integrity by reducing both oxidative stress and inflammation.